The accuracy of physician interpretation of PPG vs single-lead ECG vs 12-lead ECG for the detection of atrial fibrillation. (24th May 2021) - Gruwez, H; Evens, S; Proesmans, T; Duncker, D; Linz, D; Heidbuchel, H; Manninger, M; Vandervoort, P; Haemers, P; Pison, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The increasing availability of smartphones has enabled rhythm monitoring in large populations using standalone photoplethysmography (PPG) apps or singe-lead electrocardiography (ECG) with add-on devices. Current guidelines note that when atrial fibrillation (AF) is suspected by an automated algorithm, confirmation on an ECG tracing is required. The use of PPG alone to establish the diagnosis is not generally accepted, even when overread. The performance of physicians to discriminate between sinus rhythm (SR) and AF based on PPG alone is unknown. Purpose: To study the performance of physicians to detect AF based on PPG vs single-lead ECG vs 12-lead ECG, and to explore the incremental value of a tachogram, Poincaré plot, and algorithm output to the interpretation of the PPG waveform by physicians. Methods: PPG, single-lead ECG and 12-lead ECG data were simultaneously recorded in 30 patients. Diagnostic reference was the 12-lead ECG, read by two cardiologists. Cardiologists, electrophysiologists and cardiology fellows were invited to analyse the data of 30 patients (10 in SR, 10 in SR with extrasystoles and 10 in AF) through online surveys and classify the readings as 'SR', 'ectopic/missed beats', 'AF', 'flutter' or 'unreadable'. For dichotomous analysis, 'unreadable' was reclassified as incorrect, the other options were reclassified as AF 'present' or 'absent'. In the first survey, PPG data were presented subsequently as a waveform, stepwise adding the tachogram and Poincaré plot, and algorithm information. In the next two surveys, the single-lead and 12-lead ECG traces were presented. Sensitivity and specificity for all presentations were calculated with respect to the reference diagnosis. Diagnostic performances were compared with the Obuchowski-Rockette's ANOVA approach with Jackknife covariance estimation and Benjamini-Hochberg correction. Results: Sixty-five physicians completed the PPG survey and analysed the PPG waveforms with 88.8% sensitivity and 86.3% specificity for AF. The diagnostic metrics significantly increased to 95.5% sensitivity (P < 0.001) and 92.5% specificity (P < 0.001) after providing the tachogram and Poincaré plot. Fifty-seven physicians completed both ECG surveys and analysed the single-lead ECG outputs with 91.2% sensitivity and 93.9% specificity, while 12-lead ECG outputs were analysed with 93.9% sensitivity and 98.6% specificity. Hence, qualitative analysis of a PPG waveform with tachogram and Poincaré plot had a similar diagnostic performance to detect AF compared to single-lead ECG analysis and a similar sensitivity (P = 0.792) but lower specificity (P = 0.035) compared to 12-lead ECG. Conclusions: PPG rhythm recordings, analysed by physicians as a waveform in combination with the corresponding tachogram and Poincaré plot, achieve similar diagnostic accuracy as single-lead ECG to detect AF.